Contractual Gaps in Ijarah Maushufah fi al-Dzimmah within Pre-Order Real Estate Schemes - Kasih, Bella Mutiara; Hidayati, Tri (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
The Ijarah Maushufah Fi Al-Dzimmah (IMFZ) contract is a form of ijarah contract used in property pre-order transactions, where the benefits of the goods are promised before the object of the contract actually exists. Despite having a strong sharia basis, the implementation of this contract in the Indonesian real estate industry often creates gaps, both legally and in practice in the field. This study aims to analyze the factors that cause this gap and evaluate its impact on consumers. The method used is a qualitative approach with descriptive analysis, through data collection from official documents such as DSN-MUI fatwas, BPS reports, and relevant case studies. The results of the study indicate that many developers do not fulfill the principles of prudence and transparency as stipulated in the DSN-MUI fatwa No. 112/DSN-MUI/IX/2017 and the Regulation on the Protection of Business Actors and Consumers, thus potentially harming consumers. In addition, the inconsistency between contract practices and sharia principles and weak regulations are the main factors in the gap. Thus, it requires stricter supervision, education for consumers, and collaboration between developers, Islamic financial institutions, and regulators to create a fairer and more trustworthy Islamic property ecosystem